Residential Hybrid Ventilation Systems in Portugal:Experimental Characterization - Pinto, Manuel (2014)
Due to the variation in natural factors, such as wind speed and the stack effect, natural ventilation systems are unlikely to provide permanent ideal ventilation rates. As such, this paper will characterize the performance of hybrid ventilation systems that are a possible solution to this drawback. This project presents the experimental study characterizing the hybrid ventilation system in a 100- apartment residential complex in the Porto area. The results of the measurements of temperature, humidity, flow rates in ducts, ACH by the PFT technique and weather conditions taken in seven flats are presented.